The effectiveness of project-based learning in developing the 21st century skills - Busnawir, Busnawir; Yuniawati, Ika; Mardiati, Mardiati; Sitepu, Ediaman (Yayasan Minang Darussalam, 2025)
The rapid evolution of technology and globalization has underscored the importance of 21st-century skills, including critical thinking, creativity, collaboration, and communication. Project-Based Learning (PBL) has emerged as a powerful instructional approach to meet these evolving educational demands. This study examines the effectiveness of PBL in fostering 21st-century skills among learners across various educational contexts. Employing a systematic review of empirical studies and experimental research, the analysis reveals that PBL significantly enhances students' problem-solving abilities, promotes innovative thinking, strengthens teamwork competencies, and improves effective communication. Furthermore, PBL environments stimulate student engagement and self-directed learning, aligning academic experiences with real-world applications. The findings suggest that integrating PBL strategies into curricula not only supports cognitive development but also equips learners with the essential skills required to thrive in the modern workforce. The study concludes with recommendations for educators to adopt flexible, interdisciplinary, and student-centered PBL models to maximize learning outcomes and skill acquisition.